KINERJA AUDITOR INSPEKTORAT DALAM FUNGSI PENGAWASAN ANGGARAN - Ismed, Ismed; Andri, Seno; Rusli, Zaili (Jurnal Ilmu Administrasi Negara, 2018)
Performance of Auditor Inspectorate in Budget Supervision Function. This study aims to determine the performance Auditor Inspectorate in the function of supervision of government budget in Kampar regency. This research uses qualitative descriptive method approach. Key informants in the research are Inspectorate Inspectorate in Kampar Regency of Riau Province, Auditor Officer, Head of Service, Head of Village and Village Head. Data collection techniques are interviews, observation, and documentation. The result of the research shows that the performance of Auditor's performance has not been done well by supervising the work unit budget of regional apparatus. This is due to the inadequate budget to support efforts to maximize the role and function of supervision and supervision of Auditor Performance.